EFEKTIVITAS PERSONAL SELLING DALAM PENJUALAN ALAT KESEHATAN DAN LABORATORIUM PASCA PANDEMI COVID-19 PT MANDIKA ATUS GRATIA BENGKULU - Amalia Oktarena; Nur Efendi (Jurnal Kompetitif Bisnis, 2023)
This study aims to determine and analyze the effectiveness of personal selling in the sale of medical and laboratory equipment at PT Mandika Atus Gratia Bengkulu. The type of research used is descriptive research with a qualitative approach. Informants in this study came from the company's internal and external parties. The technique of collecting data in this research is through in-depth interviews, literature study, observation and documentation. The data analysis technique used is interactive data analysis. The data validity technique in this study used source triangulation. The results of this study indicate that PT Mandika Atus Gratia in carrying out personal selling has 5 phase, namely approach, presentation, overcoming objections, closing sales, and follow-up/maintence. The implementation of personal selling of PT Mandika Atus Gratia has been carried out in accordance with these phase. Based on the effectiveness measurement determined by the company, the personal selling of PT Mandika Atus Gratia can be declared effective because product information is conveyed quite well, in line with the increase in sales every year reaching >50% but still with fluctuations every month. Keywords: Effectiveness, Personal Selling, Sales, Promotion, Health Equipment